Reassessing self-assessment of ability: possible influence of metacognition - Mohd. Kosnin, Azlina (2006)
This study was conducted to investigate the accuracy of self-report assessment in measuring cognitive ability, and its relationship with academic achievement and metacognitive skills. In order to do this, results of cognitive ability tests were compared to responses from self-report assessments of matched domains of ability. The discrepancy between tested and self-reported responses was then compared to academic achievement, and possible connection with metacognitive skills was examined. The study adopted a quantitative approach using cross-sectional descriptive research design. A self-report assessment of cognitive ability was developed to measure verbal, number and spatial ability by adapting several items from the MIDAS, (Shearer, 1996) and the SDQIII (Marsh, 1989) inventories. All measures were translated into the Malay language. Several sets of cognitive ability tests were used to get an objective measure of the matched abilities. The tests include a set of test that was self-developed (vocabulary test), extracts from SPM Bahasa Malaysia paper II examination as well as several tests from the Kit of Factor-Referenced Cognitive Tests (Ekstrom, French, Harman & Dermen, 1976). University achievement was measured by the students’ cumulative grade point average (CGPA). A total of 465 second year UTM students from an engineering degree programme were involved in the study. Results indicate that the accuracy of self-assessment can be questioned and possible connection with metacognitive skills was suggested. INTRODUCTION Investigating the ability of students in determining academic success is no doubt important, but in practice, intelligence or ability tests are not a normal part of the national educational practice in many countries outside the United States. What is more, attributing success or failure to cognitive ability or intelligence alone may only confirm ability or deficits (Keogh & Becker, 1973). It does not really provide information that would be helpful for interventions. The main contribution of intelligence tests should not be used to make predictions but to assist students, so much so that the American National Commission on Testing and Public Policy Testing has called for the transformation of testing in America from a gatekeeper to that of a facilitator (Harrington, 1995). The commission stated that testing programmes must change from an over-reliance on objective tests to alternative forms of assessment that help people become aware of and develop their talents.